Long-term soil quality degradation along a cultivation chronosequence in western Kenya - Moebius-Clunee, B.N.; Es, H.M. van; Idowu, O.J.; Schindelbeck, R.R.; Kimetu, J.M.; Ngoze, S.; Lehmann, Johannes; Kinyangi, James (Elsevier, 2011)
Loss of agroecosystem soil functions due to soil quality (SQ) degradation impacts Africa's agricultural viability and food security. Primary forest and farm fields deforested between 1930 and 2000 were sampled along a chronosequence on two parent materials in western Kenya. Two traditional long-term management systems were sampled: continuous low-input maize (Zea mays; Co), and kitchen garden (Ki) polyculture with organic inputs. Physical, biological, and chemical SQ indicators were measured. Degradation in Co followed exponential decay trends for most indicators (organic matter, active C, water-stable aggregates, available water capacity, electrical conductivity, CEC, pH, Ca, Mg and Zn), as well as for yield. Organic matter quality declined linearly, suggesting degradation will continue. For both parent materials and most indicators degradation of 25–93% below initial values resulted, but with ≤40% further drop below initial values and for more indicators under Co than Ki. P, Zn and possibly K accumulated over time under Ki. The extent of degradation was influenced by parent material. In conclusion, a basic accessible set of SQ indicators was successfully used to describe soil degradation dynamics under cultivation. Results suggest that regular organic inputs can significantly reduce degradation, especially of nutrient retention and soil structure, after forest conversion.